Eriugena’s Concept of Return: a Work of Nature or Grace? - KIJEWSKA, AGNIESZKA (Filozofia Chrześcijańska, 2018)
This paper tackles upon John Scottus Eriugena’s concept of the return while presenting it against the background of the Neoplatonic teaching about return (epistrophe). The return belongs to the conceptual triad: mone-proodos-epistrophe which used to serve Neoplatonic thinkers to describe the structure of reality and its dependence on the First Cause. In the system of Eriugena who bequeathed that very teaching from the Christian Neoplatonists (Pseudo-Dionysius, Maximus the Confessor, Gregory of Nyssa), we talk about the return on metaphysical and mystical level in addition to the general return (reditus generalis) and the return of the elects (reditus specialis). Eriugena indicates the cyclical processes in the whole nature but at the same time he stresses that the return is caused by divine grace and the very condition of its possibility is the fact of taking fl esh (incarnatio) and taking human nature (inhumanatio) by Jesus Christ.